Biodiversity as an ecological safety condition: The European dimension - Agnieszka Rzeńca (Comparative Economic Research. Central and Eastern Europe, 2015)
Contemporary research concerning the benefits (services) of the ecosystems (environment) confirm the rank and significance of the natural environment and its resources for shaping humanity's well-being. Particularly highlighted is the need to protection of live natural resources to preserve biodiversity, which is essential for retaining the basic ecological processes and providing the sustainability of usage of these resources. Consequently, protection of biodiversity is not only an environmental issue, but also an economic and social issue involving the well-being and quality of life of society. Thus, biological diversity is an essential condition for providing ecological safety, retaining the continuity of natural processes, and conditions the quality of life and economic potential. The main purpose of the paper is to indicate the theoretical bases of biodiversity protection from the perspective of the natural and economic sciences, and to describe the diversity of biodiversity protection levels in the EU states. A specific aim is to indicate the forms and instruments of nature conservation involved in biodiversity protection, and to carry out an overview of established nature conservation programmes in selected EU countries. In order to accomplish such a complex aim, this article presents an overview of literature found in the natural, economic and legal sciences and popular magazines presenting scientific research within the field of biodiversity. Then a comparative analysis is presented based on the statistical data coming from various international statistics resources (OECD, EUROSTAT, EEA).
Keywords: 330; biodiversity; biodiversity protection; forms of nature protection; Natura 2000; ecological safety conditions